Fatigue Life Simulation and Analysis of Aluminum Alloy Sheet Self-piercing Riveting (Fracture and Structural Integrity, 2020)
The fatigue life prediction model of self-piecing riveting components of aluminum alloy is established and the effects of roughness and residual stress on fatigue life of self-piercing riveting components is analyzed by the model. Finite element software ABAQUS and fatigue analysis software FE-SAFE are used to study the effects of roughness and residual stress on the fatigue life of self-piecing riveting components through finite element simulation and mathematical statistics multivariate orthogonal regression experiment. The quantitative relations between fatigue life and three variables (roughness, residual stress and maximum stress) are fitted, and the variation trend of fatigue life with roughness and residual stress is obtained. The order of influence of roughness, residual stress, maximum stress and two interactions on fatigue life is as follows: residual stress, interaction between roughness and residual stress, roughness. When the maximum stress is fixed, the fatigue life decreases with the increase of roughness with a certain residual stress, and the fatigue life decreases with the increase of roughness with a certain residual stress. The average error between the fatigue experiment results and the simulation results is 9.74%, which proves that the simulation results are reliable.
Keywords: Aluminum alloy; Self-piecing riveting; Surface roughness; Residual stress; Fatigue life; FE-SAFE